Dynamic Information System for Failure Analysis with It’s Application on Ship Main Engine - Wolfgang Busse; Nurhadi Siswantoro; Muhammad Naufal Bintang (International Journal of Marine Engineering Innovation and Research, 2023)
Ships are often used to move cargo, and their main engines are crucial. Accidents and financial losses might result from the main engine being in poor condition. Before completing maintenance, conducting a failure analysis is necessary. The existing method is static and involves using a list of failure modes from the engine's manufacturing phase. This study proposes a preliminary design of dynamic system prototype that seeks to improve ship engine monitoring of status. It includes features such as a list of failure modes and codes based on ISO 14224:2016, data collection unit worksheet, and dynamic charts for visualizing the results. Two testing iterations were performed on the prototype. First, literature data obtained from the internet was used to generate annual and monthly report charts, confirming the functionality of the prototype. Second, real data from engine failures on the tanker ship were used to ensure logical correlations among failure causative factors. The result from real data testing included Structural Deficiency (STD), External Leakage Fuel (ELF), and Breakdown (BRD) were shown. Based on these results through the prototype simulation, can be taken into consideration for the ship's crew and shipping company management to plan oil monitoring, heating the oil properly, and conduct routine maintenance check as a preventive action to reduce the impact of engine damage in the future due to Engine Breakdown and Structural Defiency.